Increased Serum C3 and Decreased UA in Patients of Bipolar Disorder in Chinese Han Population - Yang, Xiudeng; Tao, Huai; Xiao, Ledong; Li, Cunyan; Tang, Yamei; Liu, Yong (Frontiers in Psychiatry, 2018)
The aim of this study is to explore the changes and clinical significance of serum C3, C4, hypersensitive C-reactive protein (hsCRP) and uric acid (UA) in patients of bipolar disorder (BD). In this case-control study, we recruited 141 BD patients from The Second Xiangya Hospital, Central South University, and 151 age and gender matched healthy controls (HC) from the health management central of The Second Xiangya Hospital. These patients were divided into two subgroups based on medicines use: 91 patients were treated with psychiatric drugs and 50 patients were drugs free, or four subgroups based on mood states: 54 patients in manic/hypomanic phase, 30 patients in depressive phase, 52 patients in euthymic phase and 5 patients in mixed phase. Serum levels of C3, C4, hsCRP and UA were measured in all subjects. The serum C3 levels in BD patients (0.9981±0.1849 g/L) were significantly lower than that in HC group (1.0637±0.2186 g/L), especially the drugs free subgroup and the euthymic subgroup (0.975±0.153 and 0.983±0.182 g/L), while the serum UA levels were significantly higher (354.6±90.4 vs 332.9±88.7 μmol/L), especially the drug-treated subgroup and manic/hypomanic subgroup (361.56±93.20 and 376.70±88.89 μmol/L), and rates of hyperuricaemia (31.91% vs 17.88%) were significantly higher in BD patients than in HC group. The serum C4 and hsCRP levels in HC group showed no significant difference with BD patients in whole or those subgroups. These findings suggested that the complement and purinergic systems of BD patients might be disrupted, the UA levels could be a potential marker in manic phase and the C3 might be the marker of therapeutic evaluation of BD patients.